A Brief Review on the Electrical Resistivity Of Aluminium Alloy and its Nanoparticles at Low Temperature - Khalid, Inzamam (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2022)
The objective of this review article is to study the resistivity of aluminium alloy at low temperatures. Various articles have been thoroughly studied for this review. Alloys that contain Al as dominant metal are termed as Al alloys. The first conventional Al alloy was prepared A6160 whose major constituents are Si and Mg. Al metal in its pure form has very high electrical conductivity but it is soft. Foils and conductor cables are made of Al. For advanced applications, Al is alloyed. The review has briefly explained the physical background of electrical resistivity and analysis of chosen material, aluminium alloy. Furthermore it has also discussed the resistivity of nanoparticles of Aluminium alloy.Keywords: Aluminium alloys, electrical resistivity, temperature, impurity.